IsoDGR‐Tagged Albumin: A New αvβ3 Selective Carrier for Nanodrug Delivery to Tumors. Issue 5 (12th November 2012) - Curnis, Flavio; Sacchi, Angelina; Longhi, Renato; Colombo, Barbara; Gasparri, Anna; Corti, Angelo
<x xml:space="preserve">Abstract</x> A new cyclic peptide containing the isoDGR motif that, after coupling to albumin, selectively binds αvβ3, an integrin overexpressed in the tumor vasculature. IsoDGR‐tagged albumin binds tumor vessels and can be exploited as a carrier for the preparation of tumor vasculature‐selective nanomedicines, such as gold nanoparticles (Au) carrying tumor necrosis factor α (TNF), a potent vascular damaging agent. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>